2003
DOI: 10.1038/sj.ijo.0802371
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hormone replacement therapy on weight, abdominal fat distribution, and lipid levels in Japanese postmenopausal women

Abstract: OBJECTIVE:To investigate the effects of hormone replacement therapy (HRT) on weight, abdominal fat distribution, and fasting lipid levels in Japanese postmenopausal women (PMW). DESIGN: Prospective, 12-month-controlled clinical comparison of women with and without HRT. SUBJECTS: In all, 35 PMW with HRT (conjugated estrogens, 0.625 mg daily; medroxyprogesterone acetate, 2.5 mg daily; HRT group) and 26 PMW without HRT (control group). MEASUREMENTS: Weight, abdominal fat distribution by computed tomographic measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
1
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 59 publications
1
39
1
1
Order By: Relevance
“…Estrogen replacement alone, or in combination with progesterone can prevent menopause-induced gains in adipose tissue mass (13)(14)(15)(16)(17)(18)(19). For example, women randomized to hormone replacement therapy in the Women's Health Initiative were leaner, more insulin sensitive, and less likely to develop Type 2 diabetes than women randomized to placebo (20).…”
Section: Estrogen (E2)mentioning
confidence: 99%
“…Estrogen replacement alone, or in combination with progesterone can prevent menopause-induced gains in adipose tissue mass (13)(14)(15)(16)(17)(18)(19). For example, women randomized to hormone replacement therapy in the Women's Health Initiative were leaner, more insulin sensitive, and less likely to develop Type 2 diabetes than women randomized to placebo (20).…”
Section: Estrogen (E2)mentioning
confidence: 99%
“…28,[38][39][40] Some observational studies and clinical trials have reported the association of use of hormonal therapy with lower waist-to-hip ratio or central body fat distribution. 5,17,38,[41][42][43][44][45] Changes in body fat distribution during menopausal transition could thus be related to the dynamics of estrogens, SHBG or the relative androgenicity, which are modified by the menopause transition. 8,46 The SWAN study has noted a lower estrodiol and SHBG concentration in Chinese-American women who also had comparatively lower mean BMI values.…”
Section: Menopausal Transition and Body Composition Sc Ho Et Almentioning
confidence: 99%
“…[1][2][3][4] Studies have noted the adverse changes in body composition and fat distribution, including loss of lean mass, [5][6] increase in fat mass [6][7][8][9] and redistribution of fat from periphery to the center 7-10 during midlife.…”
Section: Introductionmentioning
confidence: 99%
“…In women, the menopause is associated with increased concentrations of TC, TG, LDL and decreased concentrations of HDL. 40 In the present study, TG and HDL levels were increased in ovariectomized rats treated with 17α-ethynylestradiol, but there were no significant differences in TC and LDL levels. Camara et al 25 and Antunes et al 41 indicated that in ovariectomized rats there were no significant changes in the levels of TC and LDL as in our present study.…”
Section: Discussionmentioning
confidence: 63%